Promoting long-acting reversible contraception among post-abortion clients with a provider-comparison intervention: a cluster randomized controlled trial in Nepal - Jeremy Barofsky; Hannah Spring; Pragya Gartoulla; Raman Shrestha; Sabitri Sapkota; Elizabeth McElwee; Kathryn Church; Saugato Datta; Karina Livingston (BMC, 2024)
Abstract Background Although long-acting reversible contraception (LARC) is more effective and longer lasting than short-acting methods, uptake remains low among post-abortion clients. Using a stepped-wedge, cluster-randomized trial, we evaluate the impact of a provider-level peer-comparison intervention to encourage choice of LARC in Nepal among post-abortion clients. Methods The intervention used prominently displayed monthly posters comparing the health clinic's previous month performance on LARC uptake against peer clinics. To understand how the intervention affected behavior, while ensuring voluntarism and informed choice, we used mystery client visits, in-depth provider interviews, and client exit survey data. The trial examined 17,680 post-abortion clients in 36 clinics in Nepal from July 2016 to January 2017. The primary outcome was the proportion of clients receiving LARCs. Statistical analysis used ordinary least squares (OLS) regression with ANCOVA estimation to assess the intervention's impact on LARC uptake while controlling for client- and clinic-level characteristics. Results The intervention increased LARC use among post-abortion clients by 6.6% points [95% CI: 0.85 to 12.3, p-value < 0.05], a 29.5% increase in LARC use compared to control clinics. This effect persisted after the formal experiment ended. Analysis of provider and client experiences showed that the behavioral intervention generated significant change in providers' counseling practices, motivated the sharing of best practices. Quality of care indicators either remained stable or improved. Conclusion We find that a provider-level behavioral intervention increases LARC uptake among post-abortion clients. This type of intervention represents a low-cost option to contribute to reducing unmet need for contraception through provider behavior change.